The confident mind : a battle-tested guide to unshakable performance - Zinsser, Nathaniel (Penguin Books, 2023)
A US army psychologist shows how to acquire total self-belief when you need it most. The Confident Mind is a complete guide to self-belief for professionals in any field: how to understand it, how to build it, how to protect it and how to apply it when your performance matters. Nathaniel Zinsser has spent decades helping Army elites, Olympic and top-tier athletes and business professionals overcome self-doubt so that they can perform to the best of their ability. In The Confident Mind Zinsser shares his a step-by-step logical approach to building confidence and breaks the process down into easy-to-practice steps that everyone can utilise. Zinsser dispels the notion that confidence is instinctive or elusive, and clearly describes the process of applying self-belief when it's time to step into the spotlight. Throughout the book, readers will hear from champion athletes, army combat veterans and other elite performers and professionals to show how the reader can adopt the same mental strategies to control what can be controlled and to be unfazed by what can't.